(untitled) (Revista de Ciências Agroveterinárias, 2005)
Three experiments were conducted at lab conditions to evaluate the effects of hydrophobic extracts from sorghum roots (0; 22,3; 44,7; 89,5; 179 and 358 ppm) and hydrophilic extracts from sorghum and pearl millet shoots and roots (0; 0,5; 1,17; 1,84 and 2,5% p/v) on lettuce germination speed and shoot and root growth. Hydrophobic extracts were obtained from roots of BR 304 sorghum genotype, while hydrophilic extracts from shoots and roots from BR 304, BR 601 and RS 11sorghum genotypes and from Comum RS pearl millet cultivar. Sorghum hydrophobic extracts did not affect the speed and total germination of lettuce seeds. The increase in the concentration of sorghum hydrophobic extracts decreased lettuce root and shoot length. The effects of sorghum hydrophilic root extracts on lettuce germination, root and shoot length ranged from stimulatory, neutral or inhibitory depending on the cultivar and extract concentration used. The toxicity of pearl millet shoot extracts was usually higher than sorghum shoot extracts. Hydrophilic extracts from sorghum shoots were more inhibitory to lettuce germination, shoot and root length than hydrophilic extracts from sorghum roots. At the concentration that best discriminate the shoot hydrophilic effect (1,17%), BR 601 was the sorghum cultivar that caused more inhibition to lettuce germinability, germination speed and shoot length.